STRATEGIES FOR DEVELOPING MATERIALS IN LANGUAGE TEACHING - D.M. Jurayeva (Modern World Education: New Age Problems – New solutions, 2026)
This article explores strategies for creating teaching materials in foreign language education, emphasizing learner-centeredness, needs analysis, cultural relevance, and technology use. It highlights how teaching materials serve as key elements that influence classroom interaction, student motivation, and speaking ability. Using established theories of language teaching and curriculum design, the study stresses the importance of customizing and enhancing materials to match learners’ age, skill level, learning objectives, and cultural background. A qualitative, classroom-based approach is used to examine how teacher-created and adjusted materials impact student engagement and language use in real communicative settings. The findings indicate that materials that are context-aware, culturally sensitive, and supported by digital resources greatly boost learners’ motivation, involvement, and overall language learning success. The article concludes that systematic and reflective development of materials is crucial for improving language education quality and preparing learners for real-life and global communication.